ANALISIS NON PERFORMING LOAN DAN PENERAPAN RESTRUKTURISASI KREDIT PADA PERBANKAN SYARIAH DALAM KAITANNYA DENGAN PENGEMBANGAN EKONOMI SYARIAH DI KOTA MALANG (Study Kasus pada Perbankan Syariah dan Pedagang Kecil di Kota Malang) - Firmansyah, Fani; Widiati, Putri Kurnia (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This study analyzed the value of Non Performing Loan and credit restruction of Syariah Bankingand the relation ship with Syariah Economic growth on Malang., because credit have an important position onIndonesian Syariah Economics.Population of this research are Indonesian Syariah Banking and Small Enterpriseon Indonesia from 2007–2013 with Non Performing Loan and interview method to analyzed. To get the goodcondition of credit for small enterprise on Syariah Banking, all of the component must have a good relationship,comitment to having trust from investor or Syariah Banking. Syariah Banking must introduce acreditrestrukturization to take a part of smal enterprise growth.